2019
DOI: 10.1002/jca.21745
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis in nonmobilized donors for cellular therapy protocols: Evaluation of factors affecting collection efficiency of cells

Abstract: Introduction Collection efficiency (CE1) of cells refers to the number of cells that are collected from the total number of cells processed by the apheresis device. Limited data are available about the CE1 of cells when performing leukocytapheresis in nonmobilized donors for cellular therapy purposes. The aim of our study was to evaluate donor‐ and procedure‐related characteristics that might influence the CE1 of cells. Material and Methods Variables that predicted the CE1 of cells were analyzed by longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…In a previous study, our group observed that collection of cells using a central line was associated with lower CE1 of MNCs [10].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In a previous study, our group observed that collection of cells using a central line was associated with lower CE1 of MNCs [10].…”
Section: Resultsmentioning
confidence: 81%
“…Adverse events during apheresis, such as hypotension, bleeding, symptomatic hypocalcaemia or allergic reactions, were collected from medical records. TBV to process was calculated, either using the CE1 formula previously reported by our group [10]…”
Section: Apheresismentioning
confidence: 99%
“…Experienced apheresis nurses followed the manufacturerʼs instructions to perform apheresis procedures as previously reported . Mononuclear cell collection with an apheresis device (Cobe Spectra, TerumoBCT) was used from 2007 to 2015, and continuous mononuclear cell collection with a different apheresis device (Spectra Optia, TerumoBCT) was used from 2016 onwards.…”
Section: Methodsmentioning
confidence: 99%
“…Experienced apheresis nurses followed the manufacturerʼs instructions to perform apheresis procedures as previously reported. 13 Mononuclear cell collection with an apheresis device (Cobe Spectra, TerumoBCT) was used from 2007 to 2015, and continuous mononuclear cell collection with a different apheresis device (Spectra Optia, TerumoBCT) was used from 2016 onwards. The quantity of blood to process was calculated to obtain a target of 2 × 10 6 /kg CD34+ cells with use of the CD34+ cell count in peripheral blood sampled immediately before starting the apheresis procedure and the historical CE1.…”
Section: Apheresis Proceduresmentioning
confidence: 99%
“…Depending on the platform selected, the characteristics of the product collected might vary significantly. For instance, if an Amicus separator (Fresenius-Kabi, Bad Homburg, Germany) is used, the platelet content is very low in comparison to Spectra Optia (Terumo BCT, Lakewood, CO, USA) (Cid et al 2019), see Table 6.3. -Check if the total blood volume of the patient requires priming of the apheresis separator.…”
Section: Table 62 Designing Apheresis Collectionmentioning
confidence: 99%